Penentuan Faktor Koreksi Panjang Loncatan Hidrolik pada Kolam Peredam Energi Tipe Bucket - Nanang Saiful Rizal; Aditya Surya Manggala; Mokh Hairul Bahri; Nely Ana Mufarida; Hardian Oktavianto; Habibatul Azizah Al Faruq; Dewi Lusiana; Agung Nilogiri; Aji Brahma Nugroho; Sofia Ariyani (Institut Teknologi Bandung, 2023)
Abstrak Pada kolam olak tipe bucket, jari-jari (R) mempengaruhi loncatan hidrolik. Faktor koreksi panjang loncatan yang dipengaruhi oleh jari-jari kolam bucket. Nilai tersebut dapat digunakan menentukan panjang atau luas area pengamanan hilir sungai agar tidak terjadi tergerusan. Uji model fisik dilakukan dengan flum, panjangnya 4,1 m, lebar flume 0,15 m dan tinggi flume 0,24 m. Maka 3 variasi jari-jari kolam olak yaitu R1 = 6 cm, R2 = 7 cm dan R3 = 8 cm kemudian dialirkan air dengan 27 variasi percobaan. Diukur tinggi muka air diatas mercu bendung (Hd), saat meloncat (y1), setelah meloncat (y2) dan panjang loncatan hidrolik (Lj), didapatkan tinggi air saat meloncat (y1) dan bilangan Froude (Fr). Dengan memodifikasi persamaan Silvester (σ = 3,0 dan Ƞ = 1,17). panjang loncatan hidrolik mendekati hasil observasi dengan tingkat kesalahan relatif ΔE = 25,8%, NSE = 0,9, MAE = 6,0 dan RMSE = 3,1. Kata-kata Kunci: Kolam olak, tipe bucket, loncatan hidrolik, bilangan froude. Abstract In a bucket type still pond, radius (R) affects the hydraulic jump. The jump length correction factor is affected by the bucket pool radius. This value can be used to determine the length or area of the river downstream safeguard area so that erosion does not occur. The physical model test was carried out with a flume, the length of which was 4.1 m, the flume width was 0.15 m and the flume height was 0.24 m. Then 3 variations of the radius of the stilling pond, namely R1 = 6 cm, R2 = 7 cm and R3 = 8 cm then water was flowed with 27 experimental variations. Measured the water level above the crest of the weir (Hd), when jumping (y1), after jumping (y2) and the length of the hydraulic jump (Lj), obtained the water height when jumping (y1) and the Froude number (Fr). By modifying Silvester's equation (σ = 3.0 and Ƞ = 1.17). hydraulic jump length is close to the observed results with relative error rates ΔE = 25.8%, NSE = 0.9, MAE = 6.0 and RMSE = 3.1. Keywords: Stilling pond, bucket type, hydraulic jump, froude number. Abstract In a bucket type still pond, radius (R) affects the hydraulic jump. The jump length correction factor is affected by the bucket pool radius. This value can be used to determine the length or area of the river downstream safeguard area so that erosion does not occur. The physical model test was carried out with a flume, the length of which was 4.1 m, the flume width was 0.15 m and the flume height was 0.24 m. Then 3 variations of the radius of the stilling pond, namely R1 = 6 cm, R2 = 7 cm and R3 = 8 cm then water was flowed with 27 experimental variations. Measured the water level above the crest of the weir (Hd), when jumping (y1), after jumping (y2) and the length of the hydraulic jump (Lj), obtained the water height when jumping (y1) and the Froude number (Fr). By modifying Silvester's equation (σ = 3.0 and Ƞ = 1.17). hydraulic jump length is close to the observed results with relative error rates ΔE = 25.8%, NSE = 0.9, MAE = 6.0 and RMSE = 3.1. Keywords: Stilling pond, bucket type, hydraulic jump, froude number.